Zadanie w załączniku.
![Zadanie W Załączniku class=](https://pl-static.z-dn.net/files/dbb/1edba9c0ae776bdd40b6a54fc1d532d8.jpg)
Zadanie
a)
-(-z + 7) - (-3 - 2z) = z - 7 + 3 + 2z = 3z - 4
b)
6 - (a + 2b) + (3b - a) = 6 - a - 2b + 3b - a = -2a + b + 6
c)
7 - (-z + 9) = 7 + z - 9 = z - 2
Zadanie
(7 + 4ab - a) - (12ab + a - 13) = 7 + 4ab - a - 12ab - a + 13 = -2a - 8ab + 20
(6x + 4y + 5z) - (y + z) + (2x - 3y) = 6x + 4y + 5z - y - z + 2x - 3y = 8x + 4z
Zadanie
x = 7
(x² + 1) - (x² - x) + 10 = (7² + 1) - (7² - 7) + 10 = (49 + 1) - (49 - 7) + 10 =
= 50 - 42 + 10 = 8 + 10 = 18